Supporting Knitwear Design Using Case-Based Reasoning - Richards, P.; Ekárt, A. (Cranfield University Press, 2009)
Knitwear design is a creative activity that is hard to automate using the computer. The production of the associated knitting pattern, however, is repetitive, time-consuming and error-prone, calling for automation. Our objectives are two-fold: to facilitate the design and to ease the burden of calculations and checks in pattern production. We conduct a feasibility study for applying case-based reasoning in knitwear design: we describe appropriate methods and show how they can be implemented.
Organised by: Cranfield University
Keywords: computer-aided design (CAD); case based reasoning; knitwear design; similarity; adaptation